Assessing the Condition of Coral Reefs and the Indicator Fish (Family: Chaetodontidae) in Coastal Waters of Jayapura City, Papua Province, Indonesia - Baigo Hamuna (European Journal of Ecology, 2019)
The aim of this study was to find out the condition of coral reef coverage and the presence of Chaetodontidae fish in coastal waters of Jayapura City, Indonesia. The observation of coral reef coverage was performed using point intercept transect (PIT) method; meanwhile the observation of the presence of Chaetodontidae fish used visual census method. The result of this study described that coral reef condition in the study site was in severely damage (live coral 0%) in the DOK II site at 6 m depth, moderately damage (live coral 32.00% ±  2.13% to 42.00% ± 13.18%) in Kayu Pulo Island and the DOK II at 3 m depth, and good condition (live coral  56.00% ± 7.48% to 60.00% ± 5.55%) in the Tanjung Kayu Batu. There were 9 Chaetodontidae fish species from  Chaetodon genus, Forcipiger genus, and Heniochus genus. The number of Chaetodontidae fish was 95, of which Heniochus acuminatus was the most dominant, as many as 46 individuals.